Memorandum of understanding between Universiti Teknologi MARA, Malaysia and Chiang Mai Rajabhat University, Thailand / Fakulti Kejuruteraan Mekanikal - Universiti Teknologi MARA, Fakulti Kejuruteraan Mekanikal (Universiti Teknologi MARA (UiTM), 2021)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.